Effects of a Disability Simulation Activity on the Achievement, Efficacy, Attitudes, and Interests of Preservice Professionals. (September 2021) - Hollo, Alexandra; Brigandi, Carla B.; Jelsema, Casey M.; Shi, Mingming
Introduction: Disability simulation activities are commonly used for various purposes in higher education; however, instructors may be unaware of controversies regarding their use. The purpose of this research was to assess the effects of an activity using low vision goggles to simulate visual impairment in the context of an undergraduate course in special education. We highlight the need for instructors to consider the appropriateness of disability simulation activities given possible countertherapeutic effects.Methods: In this cluster-randomized trial, 11 classes (248 students) of preservice education and related services professionals were randomized to experimental (lecture + simulation) or control (lecture only) conditions. During a single class session, all students received basic information about visual impairment and watched a video on being a human guide. Students in the experimental group then practiced guiding and being guided while wearing low vision goggles. At the end of class, students completed three Likert-type surveys and later completed a quiz using publisher-developed materials.Results: Results showed individuals in the experimental group reported higher levels of interest and enjoyment than those in the control condition; however, there were no statistically significant differences in attitudes toward persons with visual impairments, confidence or self-efficacy for working with students with visual impairments, content knowledge, or perceptions of activity usefulness.Discussion: Findings of positive engagement in the absence of harmful effects indicate that disability simulation activities should be neither promoted nor denigrated wholesale; instead, instructors must weigh carefully potential benefits and drawbacks. Discussion includes considerations for professional education programs in using such simulations to promote skill acquisition via positive and respectful learning experiences.Implications for practitioners: Instructors who use disability simulation activities are encouraged to consider whether to discontinue this practice or incorporate principles recommended by the disability community and assess outcomes to ensure they are not perpetuating harmful stereotypes.